654 PHARYNGEAL POUCH SURGERY IN OCTO- AND NONAGENARIANS IS SAFE AND EFFECTIVE: A MULTICENTER COMPARATIVE COHORT STUDY. (17th September 2021) - Liu, David; Afzal, Mohamed; Bright, Tim; Watson, David; Devitt, Peter; Thompson, Sarah
Abstract:  : Surgery is the only effective treatment strategy for a symptomatic pharyngeal pouch. However, octo- and nonagenarians are often denied referral to a surgeon because of perceived increased risks. Here, we examine the perioperative outcomes of pharyngeal pouch surgery in octo- and nonagenarians in comparison to patients under 80 years-of-age. Methods: Analysis of a prospectively maintained database of 113 patients (≥80 years-of-age: 27, <80 years-of-age: 86) who underwent pharyngeal pouch surgery across seven hospitals from 1 January 2006 to 30 September 2020. Results: Patients ≥80 years-of-age had comparable operative time, complication profile, intensive care admission, emergency reoperation, and revisional surgery as their younger counterparts. The severity of complications was not significantly different between the two age groups. No surgical mortality was recorded. Multivariate analysis demonstrated that diverticulectomy combined with cricopharyngeal myotomy independently predicted higher rates of complications (OR: 4.53, 95% CI: 1.43-14.33, p = 0.010), but also greater symptomatic improvement (OR: 4.36, 95% CI: 1.50-12.67, p = 0.007). Importantly, a greater proportion of octo- and nonagenarians experienced improved swallowing than patients <80 years-of-age (96.3% vs. 74.4%, p = 0.013). Advanced age was not predictive of complications on multivariate analysis. Conclusion: In appropriately selected patients, pharyngeal pouch surgery can be safely offered to patients above 80 years-of-age resulting in significant improvement in their quality-of-life. These patients should not be denied surgery on the basis of advanced age alone.